Flexural design of a modular footbridge system with pretensioned carbon fiber reinforced polymer reinforcement. (27th May 2019) - Kueres, Sophia; Will, Norbert; Hegger, Josef
Abstract: A common problem of concrete footbridges are corrosion damages of the steel reinforcement. The related loss of capacity as well as visual damages often require expensive and elaborate refurbishment or even reconstruction. To overcome these drawbacks, a modular footbridge system without steel reinforcement is developed. The application of noncorrosive carbon fiber reinforced polymer (CFRP) reinforcement is suitable for building slender constructions, which are durable and long‐lasting. For the elements of the modular bridge system CFRP reinforcement is applied as mesh fabrics and pretensioned tendons. To enhance the durability and reduce costs, high strength concrete (HSC) with a high density is applied. Another advantage of the high density is that no additional surface is required. The modular construction method allows for fast assembly and disassembly of the footbridge. In this paper, the dimensioning and flexural design of the modular footbridge system are presented. In a first step, the requirements regarding cross sections, spans, and level of prestressing are defined based on natural conditions and applied loads. The results are analyzed considering the realization of a modular construction. In a second step, the flexural design of the pretensioned footbridge is presented. In this context, a flexural design model for beams pretensioned with CFRP tendons based on Eurocode 2 is developed.